Scaling up ecosystem services values: methodology, applicability and a case study - Luke M. Brander; Andrea Ghermandi; Onno Kuik; Anil Markandya; Paulo A. L. D. Nunes; Marije Schaafsma; Alfred Wagtendonk (Fondazione Eni Enrico Mattei (FEEM), 2010)
The approach of using existing data on economic values of local ecosystem services for an assessment of these values at a larger geographical scale can be called 'scaling up'. In a scaling-up exercise, economic values from a particular study site are transferred to another geographical setting, for instance to the regional, national or global scale. This paper proposes a methodology for scaling up ecosystem service values to a European level, assesses the availability of data for conducting this method, and illustrates the procedure with a case study on wetland values. The proposed methodology makes use of meta-analysis to produce a value function that is subsequently applied to individual European wetland sites. Site-specific, study-specific and context-specific variables are used to define a price vector that captures differences between sites and over time. The proposed method is shown to be practicable and to produce reasonably reliable aggregate value estimates.
Keywords: C81; Q24; Q57; 330; Ecosystem Services; Value Transfer; Meta-Analysis; Wetland Values